2002
DOI: 10.1128/jvi.76.21.10608-10616.2002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Quantitation of Species C Adenovirus DNA in Human Mucosal Lymphocytes

Abstract: The common species C adenoviruses (serotypes Ad1, Ad2, Ad5, and Ad6) infect more than 80% of the human population early in life. Following primary infection, the virus can establish an asymptomatic persistent infection in which infectious virions are shed in feces for several years. The probable source of persistent virus is mucosa-associated lymphoid tissue, although the molecular details of persistence or latency of adenovirus are currently unknown. In this study, a sensitive real-time PCR assay was develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
287
4
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 287 publications
(316 citation statements)
references
References 36 publications
21
287
4
4
Order By: Relevance
“…Of 1187 unique samples in four large studies, 64 (5.4%) contained adenoviral DNA ( Van den Veyver et al, 1998;Wenstrom et al, 1998;Baschat et al, 2003;Reddy et al, 2005), which compares favourably with 6% adenovirus DNA-positive samples among the normal controls in the present study (Table 1). And, as is the case with children infected post-natally, adenoviral DNA is retained in latently infected T lymphocytes for years following primary infection (Garnett et al, 2002). Thus, the finding of species C adenovirus in neonatal blood spots is evidence of prenatal infection, as is the case for other prenatal viral infections (Barbi et al, 1996;Johansson et al, 1997;Fischler et al, 1999).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Of 1187 unique samples in four large studies, 64 (5.4%) contained adenoviral DNA ( Van den Veyver et al, 1998;Wenstrom et al, 1998;Baschat et al, 2003;Reddy et al, 2005), which compares favourably with 6% adenovirus DNA-positive samples among the normal controls in the present study (Table 1). And, as is the case with children infected post-natally, adenoviral DNA is retained in latently infected T lymphocytes for years following primary infection (Garnett et al, 2002). Thus, the finding of species C adenovirus in neonatal blood spots is evidence of prenatal infection, as is the case for other prenatal viral infections (Barbi et al, 1996;Johansson et al, 1997;Fischler et al, 1999).…”
Section: Discussionmentioning
confidence: 97%
“…Both assays amplified DNA from all species C serotypes, but not from members of other adenovirus species (A, B, D, E, and F). In some cases, samples were also tested with a quantitative real-time PCR assay (Garnett et al, 2002). As a control, PCR with a set of HLA-DQ alpha primers was performed as described (Saiki et al, 1986).…”
Section: Pcr Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…62 In a recent study, Ad DNA was frequently detected (by real-time PCR) in lymphocytes purified from tonsils and adenoids (79%) despite the fact that infectious virus was rarely observed in these same samples. 63 Using antibody depletion methods, these authors demonstrated that Ad DNA was enriched in CD8/CD4-expressing and/ or CD3-expressing T cells, while B cells expressing CD19 were devoid or depleted of Ad DNA. 63 However, as described above, lung epithelial cells may also be a site of latent/persistent Ad infection.…”
Section: Adenovirus Persistence and Latencymentioning
confidence: 99%
“…Ad5 is a common respiratory tract virus and consequently, a high proportion of the population has immunological memory in the form of anti-Ad5 antibodies. 13 In the US, the prevalence of neutralizing antibodies against Ad5 is between 33 and 60%. 14,15 Following the first dose of systemic adenoviral administration, 100% of patients test positive for anti-adenovirus antibodies and this is likely to be the case whichever serotype that is used.…”
Section: Introductionmentioning
confidence: 99%